PERLINDUNGAN KARYA CIPTA KEBAYA SEBAGAI ASET NASIONAL YANG BERNILAI TINGGI (STUDI KASUS PERLINDUNGAN HAK CIPTA TERHADAP KARYA CIPTA KEBAYA MODIFIKASI ANNE AVANTIE) - Aditya Yuli Sulistyawan (Masalah-Masalah Hukum, 2010)
Kebaya, as an Indonesian woman traditional costume, is one of the national cultural assets that its conservation should be preserved. Based on that matter, several kebaya designers have developed kebaya through some modifications making it to be fashionable clothes that are able to draw interests. One of kebaya designers developing modified kebaya is Anne Avantie. Even today, the works of kebaya by Anne Avantie have been recognized both in national and international levels through the attained achievements. It is showed by her achievement and society acknowledgment. However, together with the existence achieved by her, many plagiarisms have occurred concerning the works of kebaya by Anne Avantie. The copyright violation ofAnneAvantie's modified kebaya which is established by the plagiarism act in a lot of cases shows the highly copyrights violation of her creation. However, Anne Avantie's modified kebaya is included in the protected creation according to Article 12 letterfofthe Indonesian Copyright Act No. 19 Year 2002. Therefore, Anne Avantie, as tf?e creator of the kebaya created by her, receives exclusive rights upon the copyrights of the kebaya to prohibit other people to use those rights without any permission from its creator. The Indonesian Copyright Act No. 19 Year 2002 has been provided enough protection for any creator's creation, including modified kebaya. Thus, the awareness of involved parties in realizing the maximum law enforcement concerning copyrights is required in order to increase the desire of creators to produce their works. Beside that, we need to socialize the importance of the appreciation and protection of copyrights to the creator itself and society.